A web-based group course intervention for 15-25-year-olds whose parents have substance use problems or mental illness: study protocol for a randomized controlled trial - Tobias H. Elgán; Nicklas Kartengren; Anna K. Strandberg; Maria Ingemarson; Helena Hansson; Ulla Zetterlind; Johanna Gripenberg (BMC, 2016)
Abstract Background Depending on the definitions used, between 5 and 20 % of all Swedish children grow up with at least one parent suffering from alcohol problems, while 6 % have at least one parent who has received inpatient psychiatric care, conditions that may affect the children negatively. Nine out of ten Swedish municipalities therefore provide support resources, but less than 2 % of these children are reached by such support. Delivering intervention programs via the Internet is a promising strategy. However, web-based programs targeting this at-risk group of children are scarce. We have previously developed a 1.5-h-long web-based self-help program, Alcohol & Coping, which appears to be effective with regards to adolescents' own alcohol consumption. However, there is a need for a more intense program, and therefore we adapted Kopstoring, a comprehensive Dutch web-based psycho-educative prevention program, to fit the Swedish context. The purpose of the program, which in Swedish has been called Grubbel, is to strengthen protective factors, such as coping skills and psychological well-being, prevent the development of psychological disorders, and reduce alcohol consumption. Methods/design The aim of the current study is to evaluate the effectiveness of Grubbel, which targets 15-25-year-olds whose parents have substance use problems and/or mental illness. Specific research questions relate to the participants' own coping strategies, mental health status and substance use. The study was initiated in the spring of 2016 and uses a two-armed RCT design. Participants will be recruited via social media and also through existing agencies that provide support to this target group. The assessment will consist of a baseline measurement (t0) and three follow-ups after six (t1), 12 (t2), and 24 months (t3). Measures include YSR, CES-DC, Ladder of Life, Brief COPE, AUDIT-C, and WHOQOL-BREF. Discussion Studies have revealed that the majority of children whose parents have substance use or mental health problems are not reached by the existing support. Thus, there is an urgent need to develop, implement, and evaluate novel intervention programs and disseminate successful programs to a broader audience. This study, investigating the effects of a web-based intervention, therefore makes an important contribution to this field of research. Trial registration ISRCTN10099247 . Retrospectively registered on August 31, 2016.